ANALISIS DAN PERANCANGAN SISTEM PAKAR DIAGNOSA KARAKTERISTIK ANAK BERKEBUTUHAN KHUSUS MENGGUNAKAN METODE FORWARD CHAINING PADA SLB NEGERI 1 KOTA JAMBI - Lindawati, Lindawati; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2019)
Artificial intelligence “experts is one of knowledge, experience, and special methods, and ableto use them to solve problems or advisors.Children with special needs disabled athletes are thehad limited or remarkable, whether physical, mental-intelektual, social, and emotional, whohad significantly in the process of growth or progress compared with anak-anak other her age.Every child with the specific needs have different ciri-ciri certain of one another, and is usuallyknown consultations done parent child with special needs disabled athletes to psychologistswhich psychologist based on this, there are some of the most experienced the high cost of forconsultation with psychologist and lack of honesty parent child with special needs disabledathletes to psychologist and therefore the or wrong diagnose kadang-kadangexperience.Here awriter design systems experts who will replace knowledge psychologist to reduce kendalakendala is, as for information recommended for outside regular school the 1 kotajambiconsisting of a table admin, table students, table solution, table the diagnosis